Molecular Dynamics Calculation on the Adhesive Interaction Between the Polytetrafluoroethylene Transfer Film and Iron Surface - Zuo, Zhen; Liang, Lifen; Bao, Qianqian; Yan, Pengtao; Jin, Xin; Yang, Yulin (Frontiers in Chemistry, 2021)
During the friction process, the polytetrafluoroethylene (PTFE) adhered on the counterpart surface was known as the PTFE transfer film, which was fundamental to the lubricating performance of the PTFE. However, the adhesive interaction between the iron surface and the adhered PTFE transfer film is still unclear. In present study, molecular dynamics simulations were used to reveal the adhesive interaction between the iron surface and PTFE transfer film. Based on the atomic trajectories obtained through the molecular dynamics, the interaction energy, concentration profile, radial distribution function, and mean square displacement were calculated to analyze the structure of the interface. The negative values of the interaction energy demonstrated the adhesive interaction between the PTFE transfer film and Fe surfaces, resulting in the accumulation of the PTFE transfer film on the Fe surface. Among the (100) (110), and (111) surfaces of α-Fe (110) surface owns the strongest adhesive interaction with the PTFE transfer film. Compared with the original PTFE molecule, the chain broken PTFE, hydroxyl substituted PTFE, and carbonyl substituted PTFE exhibited stronger adhesive interaction with Fe surface. The adhesive interaction between the PTFE transfer film and Fe surfaces was mainly originated from the Fe atoms and the F atoms of the adsorbate PTFE transfer film, which was governed by the van der Waals force. The bonding distance between the Fe atom and the F atom of the adsorbate PTFE transfer film is around 2.8 Å. Moreover, the chain broken of PTFE molecule and the rise of temperature can remarkably increase the mobility of polymer chains in the interface system.